The reality of Figure and content in the design of logos, civil society organizations (Al-Academy, 2017)
Civil society organizations in Iraq have become a community hard case dispensable as the link between the state institutions and their leaders, and between citizens of different orientations and age groups, as it represents the diversity of the terms of reference and understanding of the laws and standards of Universal Declaration of Human Rights, which requires governments to provide supplies president of its citizens to live in dignity, direct and Msasha in the life of society and the dictates we scientific our role in achieving scientific benefit and transfer of expertise to the community has become imperative for the researcher to campaign in the midst of the scientific research of the slogans of those organizations and what they can bring the design process Almmntq facilities for the extrapolation of work for members of the community, and it began a researcher at the completion of his research and came to several chapters, the first chapter of which included (methodological framework), a research problem, and the importance and purpose and its borders and determine the terminology, has identified the problem of research in several questions was the most important, do you use the designer certain pro forma references in logo design helped to achieve contact?, Is the designer was able to reconcile the form and content of the hand and between the nature and work of the organization on the other hand?From here came the importance of research to contribute to the development of design logos of those organizations and to deepen the level of cultural perception and awareness of the singular and the collective body of those logos and reasoning by which the work of organizations disciplines and orientations.And ensure that the objective of the first chapter of research to reveal the reality of form and content in designing logos and civil society organizations in Iraq and its role in the expression of personal